Metode Demonstrasi Pada Pembelajaran Bidang Studi Fiqih MTSN 14 Hulu Sungai Tengah Kabupaten Hulu Sungai Tengah - Ubaidillah (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2022)
This study aims to determine the extent of the demonstration method in the field of Fiqh at MTsN 14 Hulu Sungai Tengah. The approach in this research is a qualitative approach. It is used to obtain information related to the problem under study. The author formulates a qualitative descriptive data analysis and uses a sequential and interactionist step-by-step method, namely data collection using observation, interviews and documentation. The results showed that the demonstration method had been used in the field of fiqh studies at MTsN 14 Hulu Sungai Tengah. This method is due to make it easier for students to understand the lesson. The teacher in the field of Fiqh at MTsN 14 Hulu Sungai Tengah in the application of the demonstration method first gave an explanation of the material to be demonstrated, then the teacher gave an example of doing a good and correct demonstration of the subject matter, after that the teacher ordered the students to practice again. If the demonstration carried out by students is not good and correct, the teacher immediately fixes it as an evaluation step.